2019
DOI: 10.1101/653105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The CAFA challenge reports improved protein function prediction and new functional annotations for hundreds of genes through experimental screens

Abstract: The Critical Assessment of Functional Annotation (CAFA) is an ongoing, global, community-driven effort to evaluate and improve the computational annotation of protein function. Here we report on the results of the third CAFA challenge, CAFA3, that featured an expanded analysis over the previous CAFA rounds, both in terms of volume of data analyzed and the types of analysis performed. In a novel and major new development, computational predictions and assessment goals drove some of the experimental assays, resu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

6
3

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 57 publications
1
69
0
1
Order By: Relevance
“…The function of gene products is closely correlated with its expression levels, since co-functioning genes are often co-transcribed [43]. The latest Critical Assessment of Functional Annotation (CAFA3) reported that the best computational model in predicting the proteins associated with a particular function takes advantage of expression data [44]. While PhiMRF serves as a statistical model to understand the relationship between expression and spatial organization, it would be interesting to see whether such relationship is particularly strong for certain functional groups of genes, which could potentially explain the regulation mechanism for such functions.…”
Section: Functional Gene Groupsmentioning
confidence: 99%
“…The function of gene products is closely correlated with its expression levels, since co-functioning genes are often co-transcribed [43]. The latest Critical Assessment of Functional Annotation (CAFA3) reported that the best computational model in predicting the proteins associated with a particular function takes advantage of expression data [44]. While PhiMRF serves as a statistical model to understand the relationship between expression and spatial organization, it would be interesting to see whether such relationship is particularly strong for certain functional groups of genes, which could potentially explain the regulation mechanism for such functions.…”
Section: Functional Gene Groupsmentioning
confidence: 99%
“…FunFam relatives have been found to be more functionally similar than other domain-based resources (see Supplementary Section S1; . Function prediction pipelines based on FunFams have been consistently ranked among the best function prediction methods by the international CAFA competition (Jiang et al, 2016;Radivojac et al, 2013) and more recently have been amongst the top 5 best performing methods (CAFA3; (Zhou et al, 2019)).…”
Section: Introductionmentioning
confidence: 99%
“…The official CAFA3 evaluation places our ensemble system in top-10 overall out of 68 93 participating teams and 144 submitted systems, with particularly strong performance 94 on molecular function and cellular component categories of prokaryotic proteins, where 95 the system placed 3rd and 2nd [27].…”
mentioning
confidence: 99%
“…This is of course 338 a very difficult task. As shown in all CAFA challenges [1,2,27] the accuracy of the predictions varies greatly among the organisms and different ontologies. To look beyond 340 overall system performance, we next focus on the results of our methods on these two 341 aspects: ontologies and organisms.…”
mentioning
confidence: 99%